Effective prototyping for software makers - Arnowitz, Jonathan. (Morgan Kaufmann series in interactive technologies., 2007)
Much as we hate to admit it, most prototyping practice lacks a sophisticated understanding of the broad concepts of prototypingand its strategic position within the development process. Often we overwhelm with a high fidelity prototype that designs us into a corner. Or, we can underwhelm with a prototype with too much ambiguity and flexibility to be of much use in the software development process. This book will help software makersdevelopers, designers, and architectsbuild effective prototypes every time: prototypes that convey enough information about the product at the appropriate time and thus set expectations appropriately. This practical, informative book will help anyonewhether or not one has artistic talent, access to special tools, or programming abilityto use good prototyping style, methods, and tools to build prototypes and manage for effective prototyping. Features * A prototyping process with guidelines, templates, and worksheets; * Overviews and step-by-step guides for 9 common prototyping techniques; * An introduction with step-by-step guidelines to a variety of prototyping tools that do not require advanced artistic skills; * Templates and other resources used in the book available on the Web for reuse; * Clearly-explained concepts and guidelines; * Full-color illustrations, and examples from a wide variety of prototyping processes, methods, and tools. Jonathan Arnowitz is a principal user experience designer at SAP Labs and is the co-editor-in-chief of Interactions Magazine. Most recently Jonathan was a senior user experience designer at Peoplesoft. He is a member of the SIGCHI executive committee, and was a founder of DUX, the first ever joint conference of ACM SIGCHI, ACM SIGGRAPH, AIGA Experience Design Group, and STC. Michael Arent is the manager of user experience design at SAP Labs, and has previously held positions at Peoplesoft, Inc, Adobe Systems, Inc, Sun Microsystems, and Apple Computer, Inc. He holds several U.S. patents. Nevin Berger is design director at Ziff Davis Media. Previously he was a senior interaction designer at Oracle Corporation and Peoplesoft, Inc., and has held creative director positions at ZDNet, World Savings, and OFOTO, Inc. * A prototyping process with guidelines, templates, and worksheets; * Overviews and step-by-step guides for 9 common prototyping techniques; * An introduction with step-by-step guidelines to a variety of prototyping tools that do not require advanced artistic skills; * Templates and other resources used in the book available on the Web for reuse; * Clearly-explained concepts and guidelines; * Full-color illustrations, and examples from a wide variety of prototyping processes, methods, and tools. * www.mkp.com/prototyping.